ADAM Metalloproteinase Domain 17 Regulates Cholestasis-Associated Liver Injury and Sickness Behavior Development in Mice - Almishri, Wagdi; Swain, Liam A.; D’Mello, Charlotte; Le, Tyson S.; Urbanski, Stefan J.; Nguyen, Henry H. (Frontiers in Immunology, 2022)
Disintegrin and metalloproteinase domain-containing protein 17 (ADAM17) is a ubiquitously expressed membrane-bound enzyme that mediates shedding of a wide variety of important regulators in inflammation including cytokines and adhesion molecules. Hepatic expression of numerous cytokines and adhesion molecules are increased in cholestatic liver diseases including primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC), however, the pathophysiological role of ADAM17 in regulating these conditions remains unknown. Therefore, we evaluated the role of ADAM17 in a mouse model of cholestatic liver injury due to bile duct ligation (BDL). We found that BDL enhanced hepatic ADAM17 protein expression, paralleled by increased ADAM17 bioactivity. Moreover, inhibition of ADAM17 bioactivity with the specific inhibitor DPC 333 significantly improved both biochemical and histological evidence of liver damage in BDL mice. Patients with cholestatic liver disease commonly experience adverse behavioral symptoms, termed sickness behaviors. Similarly, BDL in mice induces reproducible sickness behavior development, driven by the upregulated expression of cytokines and adhesion molecules that are in turn regulated by ADAM17 activity. Indeed, inhibition of ADAM17 activity significantly ameliorated BDL-associated sickness behavior development. In translational studies, we evaluated changes in ADAM17 protein expression in liver biopsies obtained from patients with PBC and PSC, compared to normal control livers. PSC and PBC patients demonstrated increased hepatic ADAM17 expression in hepatocytes, cholangiocytes and in association with liver-infiltrating immune cells compared to normal controls. In summary, cholestatic liver injury in mice and humans is associated with increased hepatic ADAM17 expression. Furthermore, inhibition of ADAM17 activity improves both cholestatic liver injury and associated sickness behavior development, suggesting that ADAM17 inhibition may represent a novel therapeutic approach for treating patients with PBC/PSC.